Host-Parasitoid Model With Intraspecific Competitions - Sahoo, Banshidhar; Poria, Swarup (International Journal of Engineering and Technology, 2012)
In this paper a discrete-time host-parasitoid model with intraspecific competitions is proposed. Phase portraits are drawn for different types of intraspecific competitions to notice the effects of intraspecific competitions for biologically reasonable range of parameter values. Bifurcation analysis is done with respect to instantaneous search rate as well as handling time for different types of intraspecific competitions. Many forms of complex dynamics such as chaos, periodic windows etc. are observed. The stable coexistence as well as oscillatory coexistence of host and parasitoid are shown under different types of intraspecific competitions. The Hopf point and attractor crises exist for different intraspecific competitions.